Spontaneous Globe Rupture due to Neglected Glaucoma: How can it be? Poster Presentation - Case Report - General practitioner - Firdausi, Asri Ayu; Kunhermawan, Cosmas Hascaryanto; Lestari, Chindhia Rima Rochmatika Bunga (Majalah Oftalmologi Indonesia, 2023)
Introduction: Globe rupture is usually associated with spontaneous traumatic processes with the worst prognosis. The occurrence without prior trauma is only reported in small numbers of cases. This paper will describe a globe rupture in glaucomatous eye and share our experience with its management. Case Illustration: A 66-year-old male presented to the emergency department (ED) with reddish and progressive pain in the right eye (RE) followed by severe headaches for the last three days. On history taking, the patient complained of a progressive blurry vision to total blindness of his RE for 1 year. The patient admitted to having a history of glaucoma on previous primer examination but did not routinely control it. On initial examination, the patient was hypertensive , and suddenly began bleeding within 10 minutes upon arrival at ED. The diagnosis of globe rupture was made and he underwent emergency evisceration. Discussiona: Spontaneous globe rupture is very rare, with an incidence of 3 per 100.000 in the United States, while no definite number is found in Indonesia due to the rarity. In glaucoma patients, spontaneous globe rupture is postulated to occur due to suprachoroidal hemorrhage. Our patients had multiple risk factors such as advanced age, systemic hypertension, and chronic untreated glaucoma. Evisceration went down to reduce pain, stop bleeding and prevent the spread of infection. Performing surgery within 10 days of the initial injury suggests a lower risk of post-operative endophthalmitis or sympathetic ophthalmia. Conclusion: Spontaneous globe rupture in neglected chronic glaucoma has a very poor outcome but preventable.